Effects Of Clay Modification And Compatibilizers On The Mechanical, Morphological, And Thermal Properties Of Polyamide 6/Polypropylene Nanocomposites [TN941. K97 2008 f rb]. - Kusmono, Kusmono (2008)
Nanokomposit yang mengandungi gaulan poliamida 6 (PA6)/polipropilena (PP) PA6/PP (70/30) dan organo-tanah liat (0-10 phr) telah disediakan menggunakan penyebatian leburan.